2020
DOI: 10.3390/agronomy10081067
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Evaluation of a Hybrid Diploid Blueberry Population for Plant Development and Fruit Quality Traits

Abstract: A diploid blueberry mapping population, used previously to map quantitative trait loci (QTL) for chilling requirement and cold hardiness, was evaluated for several plant development and fruit quality traits. Specifically, the population was phenotyped in a greenhouse for timing of various stages of flower bud, leaf bud and fruit development and for fruit quality traits including weight, diameter, color, scar, firmness, flavor and soluble solids. Phenotypic data was analyzed statistically by analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…A comparison of the genes associated with these SNPs to our results found that one of the genes associated with fruit size (gene.g14573.t1, hypersensitive-induced response protein 1-SPFH/Band 7/PHB domain) is located in the vicinity of a minor QTL for 3 mm Firm from our study. Interestingly, we previously found that 20S Firm was moderately correlated with fruit size (Weight and Dia) in our diploid mapping population (Rowland et al, 2020). In addition, two of the genes associated with flower bud density (CUFF13871.1 and 54064_g.1) in Ferrão et al (2018) are located in the region of a minor QTL for Dia from our results.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…A comparison of the genes associated with these SNPs to our results found that one of the genes associated with fruit size (gene.g14573.t1, hypersensitive-induced response protein 1-SPFH/Band 7/PHB domain) is located in the vicinity of a minor QTL for 3 mm Firm from our study. Interestingly, we previously found that 20S Firm was moderately correlated with fruit size (Weight and Dia) in our diploid mapping population (Rowland et al, 2020). In addition, two of the genes associated with flower bud density (CUFF13871.1 and 54064_g.1) in Ferrão et al (2018) are located in the region of a minor QTL for Dia from our results.…”
Section: Discussionsupporting
confidence: 68%
“…Fruit firmness was also evaluated in our population (Rowland et al, 2020), and a major QTL for firmness (using the 20 S Firm method) was identified on LG06 that was consistent over 3 www.Vaccinium.org 2 years. By scanning through the list of annotated genes from the diploid genome in the 20 S Firm QTL region, we identified several genes encoding alpha-glucosidases and one encoding pectin methylesterase and pectin methylesterase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations